Rút gọn Đa thức
A= xy-\(\frac{1}{3}\) x2+\(\frac{1}{5}\) y-7 x2+5 x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=x^2+4x-21-x^2-4x+5=-16\\ B=-2\left(4x^2+20x+25\right)-\left(1-16x^2\right)\\ B=-8x^2-40x-50-1+16x^2=8x^2-40x-51\\ C=x^2\left(x^2-16\right)-\left(x^4-1\right)=x^4-16x^2-x^4+1=1-16x^2\\ D=x^3+1-\left(x^3-1\right)=2\\ E=x^3-3x^2+3x-1-x^3+1-9x^2+1=-12x^2+3x+1\)
Bài 6:
c: \(9x^2+6x+1=\left(3x+1\right)^2\)
d: \(4x^2-9=\left(2x-3\right)\left(2x+3\right)\)
e: \(x^3+27=\left(x+3\right)\left(x^2-3x+9\right)\)
Ta có: \(\frac{5}{3}x^2y^4-\frac{1}{7}x^3y^2-xy+\left(\frac{1}{7}x^3y^2-\frac{5}{3}x^2y^4+\frac{1}{3}xy\right)\)
\(=\frac{5}{3}x^2y^4-\frac{1}{7}x^3y^2-xy+\frac{1}{7}x^3y^2-\frac{5}{3}x^2y^4+\frac{1}{3}xy\)
\(=-xy+\frac{1}{3}xy\)
\(=xy\left(-1+\frac{1}{3}\right)=-\frac{2}{3}xy\)
Bậc của nó là 2
\(A=\left(-\frac{1}{3}x^2-7x^2\right)+xy+\frac{1}{5}y+5x\)
\(A=x^2\left(-\frac{1}{3}-7\right)+xy+\frac{1}{5}y+5x\)
\(A=-\frac{22}{7}x^2+xy+\frac{1}{5}y+5x\)